Ultrasonic Nondestructive Evaluation Systems (Industrial Application Issues) - Burrascano, Pietro (Springer, 2015)
This book originates from a nice discussion among colleagues with different engi neering backgrounds and skills. We had so far worked in apparently distant fields, such as ultrasonics, sensing for nondestructive evaluation (NDE) of manufactured goods, signal processing for telecommunications, signal processing for earth explo ration and geophysical engineering, and more. We had been involved in these areas in various capacities, for different applications and with different goals. During our ex changes, it clearly emerged that some of the difficulties encountered in the industrial implementation of ultrasonic testing techniques could be better addressed by pursu ing a closer interaction among sibling working areas. Specifically, we realized that there were advantages in importing and adapting results or points of view originally developed in areas different from ultrasonic testing, such as telecommunications, radar, or geophysics....